Haunting legacy Vietnam and the American presidency from Ford to Obama - Kalb, Marvin L. (Brookings Institution Press, 2011)
"Examines how presidential decision making has been influenced by America's defeat in the Vietnam war, studying presidents Ford, Carter, Reagan, George H. W. Bush, Clinton, George W. Bush, and Obama and how they have approached key decisions regarding conflicts while in office"--Provided by publisher.